Observation of interaction-induced modulations of a quantum Hall liquid’s area - Sivan, I.; Choi, H. K.; Park, Jinhong; Rosenblatt, A.; Gefen, Yuval; Mahalu, D.; Umansky, V. (Nature communications, 2016)
Studies of electronic interferometers, based on edge-channel transport in the quantum Hall effect regime, have been stimulated by the search for evidence of abelian and non-abelian anyonic statistics of fractional charges. In particular, the electronic Fabry–Pérot interferometer has been found to be Coulomb dominated, thus masking coherent Aharonov–Bohm interference patterns: the flux trapped within the interferometer remains unchanged as the applied magnetic field is varied, barring unobservable modulations of the interference area. Here we report on conductance measurements indicative of the interferometer’s area ‘breathing’ with the variation of the magnetic field, associated with observable (a fraction of a flux quantum) variations of the trapped flux. This is the result of partial (controlled) screening of Coulomb interactions. Our results introduce a novel experimental tool for probing anyonic statistics. Quantum Hall liquids play host to a wide range of unusual physics. Here, the authors use an electronic Fabry-Pérot interferometer to observe modulations of a quantum Hall liquid’s area, which can offer a means to study the statistics of fractional charges.